Integrative taxonomy of Peniculus, Metapeniculus, and Trifur (Siphonostomatoida: Pennellidae), copepod parasites of marine fishes from Chile: species delimitation analyses using DNA barcoding and morphological evidence. Issue 5 (2nd September 2016) - Castro-romero, Raúl; Montes, Martín M.; Martorelli, Sergio R.; Sepulveda, Diego; Tapia, Silvia; Martínez-aquino, Andrés
Abstract : Pennellidae is a family of copepod parasites of widely distributed marine fishes. The pennellid species are usually morphologically differentiated by cephalothorax, neck, trunk, and abdomen shape. These characters, however, show high polymorphism and therefore using only this type of data, delimitation at species level of this genus is difficult. In this study, we explored the genetic distances calculated from sequences of a DNA barcoding marker (COI mt) (678 base pairs). We also explored the genetic distances of 25 Peniculus specimens associated within nine marine fish species, four Metapeniculus specimens associated within one marine fish species, and four Trifur specimens associated within one marine fish species. All specimens were collected in Antofagasta Bay, Chile and were calculated from sequences of a DNA barcoding marker (COI mt) (678 base pairs). The genetic distance among the Peniculus specimens was 0.95% from the different host species, the Metapeniculus specimens distance was 0.44% and the Trifur specimens was 2.25%. Genetic difference between Peniculus and Metapeniculus was 17.86% and Peniculus differ from T . tortuosus by 18.16%. We analysed the barcoding gene fragment using Bayesian Inference (BI) for phylogenetic reconstruction using three outgroups. Based on the phylogenetic analysis an ultrametric tree was built and a general mixed Yule-coalescent (bGMYC) model was conducted for species delimitation. Morphometrics analyses were made with Bayesian statistics. Mean and credibility limit (95%) for each parameter was calculated. Results show that based on morphology the individuals collected can be assigned to P. cf. fistula von Nordmann, 1832, Metapeniculus antofagastensis Castro-Romero & Baeza-Kuroki, 1985, and Trifur cf. tortuosus Wilson, 1917. High morphological polymorphism was observed for the lineage of Peniculus associated to several host species of marine fishes. Similar results were obtained for Trifur cf. tortuosus parasites on Chilean marine fishes.